Myrcia magnipunctata (Myrtaceae), a new species from Minas Gerais, southeastern Brazil - Verly, Otávio Miranda; Cabral-Da-Silva, Luiz Claudio Medeiros; Torres, Carlos Moreira Miquelino Eleto; Sobral, Marcos (Phytotaxa, 2025)
N/A